The Literacy Development: Unveiling the Role of Balai Poestaka: A Historical Study - Nurmalina; SA., Romli; Rochmiatun, Endang (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
The existence of Balai Poestaka was aimed to facilitate the Dutch East Indies Government in monitoring the circulation of "appropriate reading materials for the people." Therefore, on September 14, 1908, the Commissie voor de Inlandsche School en Volkslectuur (Commission for Native Schools and Public Reading), which eventually changed its name to Balai Poestaka was formed. However, the efforts made by Balai Poestaka had at least some impact on the development of literacy in various communities, including the Palembang Residency. This research aims to understand the initiatives undertaken by Balai Poestaka in advancing literacy in the Palembang Residency community. The study employs historical research methods, including heuristics, verification, interpretation, and historiography. The study reveals that at least three efforts were made by Balai Poestaka to enhance community literacy. First, the establishment of Taman Poestaka, a library dedicated to the natives, opened in native schools under the supervision of teachers. Second, the initiation of Depot van Leermiddelen and small trucks serving as mobile bookstores reached villages in Java, Sumatra, Sulawesi, and Kalimantan. Third, at least three times a year, Balai Poestaka distributed 100,000 catalogs, each consisting of 32 pages, to promote its published books. Additionally, Balai Poestaka sold its books at affordable prices to make them accessible to the purchasing power of the community.